Seals from Argishtikhinili-Armavir - Yengibaryan, Nora (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Seals were unearthed in the eastern and western fortresses of Argishtikhinili, as well as in sarcophagus, urn, and pithos burials of the necropolis adjacent to the western fortress. Argishtikhinili (western fortress) is the only place where half-made seals of various stones have been found. The discovered Urartian seals belong to the cone-shaped, bell-shaped, truncated cone and truncated pyramid types. There are also single samples made of bone; these are seals in the shape of a lion’s paw, in the form of a narrowing pole and a piece of a horn with samples of five sculpted impresses. There were also Assyrian glazed faience cylinder seals found with images of an archer, dragon and standard with a crescent. The Urartian seals are made of various types of stone and bone. On the base of the cone-/bell-shaped types of seals there were depictions of a horse, goat, the winged disc of the Sun and a griffon. Rituals at the Tree of Life and a procession of mythical animals are pictured on the samples with scenery composition. Stamps on the various ceramic vessels testify to the use of numerous other seals. The presented seals most probably were used concurrently and have been dated to the 8th-6th centuries BC.